Analysis on Student Comprehension Level to Activities of Group Guidance Service - Damayanti, Siska; Astuti, Budi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research aims to identify level of student comprehension on activities of group guidance service in SMAN 2 Banguntapan. This research is categorized into descriptive quantitative research design. This research is executed on 98 students who are then taken as the research sample, particularly who have joined the activities of group guidance service. Moreover, the research instrument is a closed questionnaire that has been through validity test in formula of product moment and reliability in formula of alpha. Next, the method of data analysis in this research exerts descriptive analysis. Due to the research findings, it is indicated that the level of student comprehension to the activities of group guidance service in low category is 15 students (15%), mediate category is 67 students (69%), and high category is 16 students (16%). Regarding to this assessment result, it is required to optimize the activities of group guidance service in order to achieve the student development, widen knowledge and information, and prevent problems that might happen in the future